2008
DOI: 10.1158/1078-0432.ccr-08-0326
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ Pathway Targeting in Carcinogenesis: Implications for Chemoprevention

Abstract: The peroxisome proliferator-activated receptor (PPAR) g is one member of the nuclear receptor superfamily that contains in excess of 80 described receptors. PPARg activators are a diverse group of agents that range from endogenous fatty acids or derivatives (linolenic, linoleic, and 15-deoxy-D 12,14 -prostaglandin J 2 ) to Food and Drug Administration-approved thiazolidinedione drugs [pioglitazone (Actos) and rosiglitazone (Avandia)] for the treatment of diabetes. Once activated, PPARg will preferentially bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 70 publications
1
92
0
1
Order By: Relevance
“…23). In our studies, proapoptotic effects were demonstrable in both p53 wt/wt and p53 wt/Ala135Val mouse models and in the SCC model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23). In our studies, proapoptotic effects were demonstrable in both p53 wt/wt and p53 wt/Ala135Val mouse models and in the SCC model.…”
Section: Discussionmentioning
confidence: 99%
“…G0S2 has been found to be frequently methylated in SCC of the lung (41), suggesting that G0S2 may have tumorsuppressive functions in the context of lung SCC. Additional mechanisms, such as induction of differentiation (24,25,27), inhibition of invasion, and inhibition of angiogenesis, may also be significant (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LXR alpha (LXRA, NR1H3) was significantly underexpressed in ACCs in three studies (Giordano et al, 2009;To¨mbo¨l et al, 2009;de Reynie`s et al, 2009) that may be related to the already described loss of chr11p11 (Figure 3; Supplementary Table 3). PPAR-g (PPARG) regulates expression of genes involved in glucose and lipid homeostasis and is implicated in the pathogenesis of several tumours (Ondrey, 2009). PPARG is expressed in normal adrenals, benign and malignant ACTs (Betz et al, 2005), and in the NCI-H295 cell line (Ferruzzi et al, 2005).…”
Section: Cholesterol and Lipid Metabolism: Rxr/lxr And Rxr/pparg Signmentioning
confidence: 99%
“…5 Despite the suggestions that TZD might favor cancer remission, there are conflicting data on whether PPARc activation promote or suppress tumorigenesis when applied in animal model of cancer. 6 Studies in colon and breast carcinogenesis have shown that TZDdependent activation of PPARc leads to an increase of tumor formation. 7,8 In addition, PPARc is overexpressed in many epithelial tumor cells and regulates the production of hepatocyte growth factor which can favor tumor growth, suggesting that this nuclear receptor might represent a prosurvival factor.…”
mentioning
confidence: 99%